Pengembangan E-LKPD Interaktif Berbasis Flipbook dengan Model Pembelajaran Inkuiri Terbimbing pada Materi Perubahan Wujud Zat Kelas IV di SDN Sukolilo Barat 01 - Husnul Khotimah; Bagus Rahmad Wijaya (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
The low involvement of students in science learning and the limited availability of interactive teaching materials are factors that cause suboptimal learning outcomes in the material on changes in the state of matter. This study aims to develop an interactive E-LKPD based on flipbooks with a guided inquiry learning model on the material on changes in the state of matter for grade IV of SDN Sukolilo Barat 01 that meets the criteria of validity, practicality, and effectiveness. The study used the Research and Development (R&D) method with the 4D model which includes the stages of define, design, develop, and disseminate. Data were collected through expert validation sheets, teacher and student response questionnaires, and learning outcome tests, then analyzed using descriptive statistics in the form of percentages and classical completeness. The results showed that the developed E-LKPD obtained an average validity of 95% (very valid), practicality of 95.5% (very practical), and increased student learning completeness from 40% to 90%. These findings indicate that flipbook-based E-LKPD with a guided inquiry model is able to increase student engagement and learning outcomes, making it suitable for use as digital teaching material in science learning in elementary schools.